Global models for a global pandemic: The impact of COVID-19 on small euro area economies - Pablo García; Pascal Jacquinot; Crt Lenarcic; Matija Lozej; Kostas Mavromatis (European Central Bank (ECB), 2021)
This paper analyses the effects of the COVID-19 pandemic shock on small open economies in a monetary union with an application to the euro area. Accounting for a high degree of openness and a strong dependence on intra and extra union trade, we focus on the size and the direction of international spillovers both from the shock itself and from the ensuing fiscal response. To do so, we use a unifted modelling framework: The Euro Area and the Global Economy (EAGLE) model. Furthermore, within this general framework, we assess the extent to which speciftc modelling features shape the dynamic responses to the COVID-19 pandemic. The main messages are as follows. First, fiscal spillovers from the rest of the monetary union do matter. Second, the effective lower bound ampliftes the size of the spillovers. Third, the design of wage negotiations leads to wage subsidies having negative international fiscal policy spillovers. Fourth, import content of government spending interacts with the effective lower bound, strongly affecting the size and sign of spillovers. Fifth, when households have finite lifetimes, the responses of output and inflation are amplifted compared to the case with infinitely lived households. Finally, a next generation EU instrument is more effective when financed using a tax on consumption.
Keywords: C53; E32; E52; F45; 330; DSGE Modelling; International Spillovers; Monetary Union; Euro Area; COVID-19